HUBUNGAN ANTARA KECERDASAN INTERPERSONAL DENGAN HASIL BELAJAR IPS SISWA KELAS IV MIN 2 PADANGSIDIMPUAN - Fazilah, Dinda; Lubis, Ilham Sahdi Lubis; Theresia, Monica (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2023)
This study aims to look at the level of interpersonal intelligence of students and social studies learning outcomes of Min 2 Padangsidimpuan students and to see whether there is a significant relationship between interpersonal intelligence and social studies learning outcomes of fourth grade students. This research was carried out at MIN 2 Padangsidimpuan, carried out in May 2023 with a total population of class IV and the sample consisted of  20 students where 9 boys and 11 girls were taken using a total sampling technique. This study uses quantitative research by applying the correlational method. The data collection technique used was a questionnaire (to measure interpersonal intelligence) and test sheets (to measure social studies learning outcomes of students). The results of the calculations in this study showed that the average level of interpersonal intelligence was 57.55 (medium category) and the average social studies learning outcomes of students was 80.75 (good category). Furthermore, based on the formula r product moment (using spss 22) shows a significant score of  0.034 and this score is less than 0.05 (0.034 < 0.05). Meaning that Ha is accepted so that there is a significant relationship between interpersonal intelligence and social studies learning outcomes for class IV MIN 2 Padangsidimpuan students